If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ay + -1C = Bx Reorder the terms: -1C + yA = Bx Solving -1C + yA = xB Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-1yA' to each side of the equation. -1C + yA + -1yA = xB + -1yA Combine like terms: yA + -1yA = 0 -1C + 0 = xB + -1yA -1C = xB + -1yA Divide each side by '-1'. C = -1xB + yA Simplifying C = -1xB + yA
| 8m-25=27 | | 2x-1y=8 | | 3x=4y+5 | | 4w+11=55 | | 11=-x+6 | | 5y=-4x+6 | | -3x=10+2x | | 2x-(x+3)=2x-11 | | -3(x+8)+3=11(x-7) | | 13-6x+14= | | X^2+60x-252=0 | | 180-3x=12x | | x(x^2-4x+75)=0 | | F(x)=4x^9 | | 8.1+9=5.1x-3 | | zi+z+1+3i=0 | | 24X+1.19=.79 | | 51=4w-17 | | 47=2u+13 | | 24X+0.79=1.19 | | -7x+2y=9fory | | x+14=4x-9 | | 2(x+3)-x+4=2(x-1)+5 | | 5u+15=60 | | 9x=4x-8+2 | | -7x+2y=9foru | | i*z+z+1+3*i=0 | | (5x-12)=2 | | 8ty=4 | | -5x^2-30x-3=0 | | z*i+z+1+3*i=0 | | 2x^2+12x-19=8-3x |